1978
DOI: 10.1515/cclm.1978.16.9.493
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Conversion of Estradiol-17β into Estrone in Normal Human Myometrium und Leiomyoma

Abstract: Summary:The specific activity of 170-hydroxysteroid dehydrogenase was measured in normal human myometrium, and in leiomyoma specimens obtained from the same tumor-bearing uterus. In all cases the normal tissue showed greater conversion of estradiol-17/3 into estrone than the neoplastic tissues. In normal myometrium of fertile women, the specific enzyme activity depended on the phase of the menstrual cycle, the highest values of 170-hydroxysteroid dehydrogenase activity being found in the early secretory phase.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

1979
1979
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…The findings of Pollowe t al. [6,7] which point to high local levels of estrogens in the myoma are in accord with a stimulatory role of estrogen as a factor contributing to the increased glycogen levels in metabolically active myomas.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The findings of Pollowe t al. [6,7] which point to high local levels of estrogens in the myoma are in accord with a stimulatory role of estrogen as a factor contributing to the increased glycogen levels in metabolically active myomas.…”
Section: Discussionmentioning
confidence: 73%
“…Nevertheless, it is difficult to understand why normal uterine muscle and myomas would react differently to the same hormonal environment. A possible explana tion was suggested by Pollow et al [6] who found that the activity of (3-hydroxysteroid dehydrogenase, which converts 17 p-estradiol to estrone, a much less potent estrogen, is lower in myomas than in surrounding muscle. These authors also found a higher estradiol-binding capacity and a lower concentration of progesterone receptors in myoma, as compared to normal myometrium [7], These findings could well explain increased estrogen effect on myomas even when the prevailing hormonal environment is low in estrogens.…”
Section: Discussionmentioning
confidence: 99%
“…Because estradiol up-regulates both of these receptors, the increased concentration of estradiol in these tumors compared with that in the myometrium (Otubu et al 1982) could be indicative of a pathogenetic link to the development of leiomyomata. The demonstration of reduced activity in leiomyomas of the enzyme 17β-hydroxysteroid dehydrogenase (Eiletz et al 1980;Pollow et al 1978b), the enzyme responsible for the conversion of estradiol to estrone, would seem to provide a plausible explanation for the accumulation of estradiol in these tumors (Otubu et al 1982). Although estrone is weakly estrogenic, it exhibits a lower binding affinity for ERs than estradiol, and it diffuses out of the cell more rapidly than estradiol.…”
Section: Review | Uterine Leiomyomamentioning
confidence: 99%
“…(2) The activ ity of 17(3-hydroxysteroid dehydrogenase in the LM is decreased [28]; this progesteroneinduced enzyme accelerates the conversion of estradiol to estrone, i.e. to a less active metab olite [29,30].…”
Section: Discussionmentioning
confidence: 99%